CXCR4 antagonist delivery on decellularized skin scaffold facilitates impaired wound healing in diabetic mice by increasing expression of SDF‐1 and enhancing migration of CXCR4‐positive cells. Issue 4 (7th August 2017) - Liu, Hao; Liu, Hanping; Deng, Xiaoyuan; Chen, Maosheng; Han, Xue; Yan, Wenxia; Wang, Ning
Abstract: C‐X‐C chemokine receptor type 4 (CXCR4) is an alpha‐chemokine receptor specific for stromal cell‐derived factor 1 (SDF‐1 also called CXCL12). The antagonist of CXCR4 can mobilize CD34+ cells and hematopoietic stem cells from bone marrow within several hours, and it has an efficacy on diabetes ulcer through acting on the SDF‐1/CXCR4 axis. In this study, we investigated for the first time whether the antagonist of CXCR4 (Plerixafor/AMD3100) delivered on acellular dermal matrix (ADM) may accelerate diabetes‐impaired wound healing. ADM scaffolds were fabricated from nondiabetic mouse skin through decellularization processing and incorporated with AMD3100 to construct ADM‐AMD3100 scaffold. Full‐thickness cutaneous wound in streptozotocin (STZ)‐induced diabetic mice were treated with ADM, AMD3100, or ADM‐AMD3100. 21 days after treatment, wound closure in ADM‐AMD3100‐treated mice was more complete than ADM group and AMD3100 group, and it was accompanied by thicker collagen formation. Correspondingly, diabetic mice treated with ADM‐AMD3100 demonstrated prominent neovascularization (higher capillary density and vascular smooth muscle actin), which were accompanied by up‐regulated mRNA levels of SDF‐1 and enhanced migration of CXCR4 in the granulation tissue. Our results demonstrate that ADM scaffold provide perfect niche for loading AMD3100 and ADM‐AMD3100 is a promising method for diabetic wound healing mainly by increasing expression of SDF‐1 and enhancing migration of CXCR4‐positive cells.